Determinants of driving among oldest-old Australian women. (4th May 2022) - Hambisa, Mitiku Teshome; Dolja-Gore, Xenia; Byles, Julie E.
ABSTRACT: This study examined predictors of driving among oldest-old Australian women in their late 80s in accordance with the World Health Organization's healthy aging framework. The study used data from the 1921–26 cohort of the Australian Longitudinal Study on Women's Health, wave-6 (n = 4025). The result of the multivariable logistic regression showed providing care, living alone, volunteering, living in rural/outer regional Australia, having higher educational attainment, and social interactions were associated with driving. The findings indicate driving should not be dismissed based on age alone. Policymakers need to also consider social roles, driving environment and context with the goals of healthy aging.